Brief introduction to the formation of a scientific spirit for a Social Communicator and Journalist - Valencia Tamayo, Luis Felipe (Escribanía, 2018)
The understanding of contemporary reality requires more journalists to help overcome the gap between scientific knowledge and societies. More than an effort to know what happens in science, that understanding of reality is linked to an epistemology that supports the development of research and scientific work. Therefore, this text appears as a brief and pedagogical introduction to the young student of Social Communication and Journalism who, confused, often stays at the gates of philosophical and humanistic debate that there are about science, refraining from participating actively in the epistemological arena and, what it is even worse, eluding responsibility to connect science with the world.